Are corporate climate efforts genuine? An empirical analysis of the climate 'talk–walk' hypothesis. (29th March 2022) - Coen, David; Herman, Kyle; Pegram, Tom
Abstract: This study conducts machine‐aided textual analysis on 725 corporate sustainability reports and empirically tests whether climate 'talk' within the sampled reports translates into performance 'walk', proxied by changes in greenhouse gas emissions over a 10‐year period. We find mixed results for the 'talk–walk' hypothesis, depending on the type of talk and the associated climate change actors involved. Indeed, our empirical models show that while some climate commitments are genuine, many constitute little more than 'greenwashing'—producing symbolic rather than substantive action. We attribute this result to false signalling of climate transitioning in order to mislead due to misaligned incentives. An unexpected positive finding of the study is that talk about operational improvements is a significant predictor of climate performance improvement. On the other hand, reactive strategies are consistent with poor climate performance. Our findings highlight the significance of corporate climate strategies other than emissions reductions in assessing the effective contribution of business to the climate transition.